Tingkat Pendidikan Ibu Dan Pola Asuh Demokratif Pada Anak Usia 4 Sampai 6 Tahun Di Tk Kuncup Harapan - Era Revika; Irma Erviana; Galuh Tunjung (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
AbstractParenting patterns will shape behavior in children. Democratic parenting will make children more independent, easy to make decisions, and more confident so that they will get success in the future. Parental education is one of the important things in life because education provides broader insight and influences good parenting for their children.This study aims to determine the correlation between mother's level of education and democratic parenting in children aged 4 to 6 years.This study used a cross-sectional method at the Kuncup Harapan Kindergarten. The subject of this research is the parents of students. The population of this study was all parents of students. 53 respondents in this study were selected using simple random sampling. The instrument in this study was a questionnaire.Results: The results of the analysis (Sig 0.017<0.05) showed a correlation between the level of mother's education and democratic parenting in students aged 4 to 6 years in Kuncup Harapan Kindergarten..Keywords: education level, democratic parenting